2021
DOI: 10.3389/fphar.2021.524663
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effect and Mechanism of Bushen-Jianpi-Jiedu Decoction Combined with Chemotherapeutic Drugs on Postoperative Colorectal Cancer

Abstract: There is a lack of effective therapeutic drugs in patients with postoperative colorectal cancer (PCRC). This study aimed to investigate the therapeutic effect and mechanisms of Bushen-Jianpi-Jiedu decoction (BSJPJDD) combined with chemotherapeutic drugs (oxaliplatin) on PCRC with liver and kidney yin deficiency and spleen deficiency syndrome (LKYD-SDS) through the therapeutic evaluation of clinical therapy and the integrative analysis of network pharmacology, RNA-seq and label-free data, and experiment verific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…However, the 5-year survival rate is low, and chemotherapy has significant hazardous side effects [6]. Hence, new treatment schemes and strategies are of great significance, and notably, TCM combined with chemotherapy has unique advantages in the prognosis of CRC patients [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…However, the 5-year survival rate is low, and chemotherapy has significant hazardous side effects [6]. Hence, new treatment schemes and strategies are of great significance, and notably, TCM combined with chemotherapy has unique advantages in the prognosis of CRC patients [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there has been a growing body of evidence supporting the widespread use of transcriptomics and proteomics in enhancing our understanding of pathophysiological mechanisms and facilitating the development of diagnostic tools for various diseases ( Li et al, 2020 ; Mu et al, 2020 ; Yang et al, 2021 ; Yang et al, 2023 ). Moreover, the utilization of weighted gene coexpression network analysis (WGCNA) offers the ability to illustrate the interconnections between diverse genes through the creation of a co-expression network, which not only enables the identification of modules that are associated with specific phenotypes but also proves to be more efficient in the investigation of crucial pathways and genes involved in numerous human disorders ( Langfelder and Horvath, 2008 ; Zhang et al, 2024 ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, researchers have conducted several studies to explore the scientificity; for example, network pharmacology research has found that different diseases have related or the same pathogenesis, and TCM can play a therapeutic role in two or more diseases by regulating these core targets ( Su et al., 2022 ). In addition, several omics studies have explored and confirmed the common characteristics of different diseases from the perspective of genes, proteins, and metabolites, and regulating these key targets is of great significance in disease treatment ( Chang et al., 2018 ; Yang, 2019 ; Liu et al., 2020 ). Moreover, we found gut microbiota disorders to also be related to the emergence and development of a variety of diseases, and restoration of the intestinal microecology may also be a potentially important link to TCM‘s therapeutic role in “treating different diseases using the same method”.…”
Section: Introductionmentioning
confidence: 99%